PEMBINAAN LEMBAGA KESENIAN OLEH DINAS KEBUDAYAAN DAN PARIWISATA KOTA PEKANBARU - Fadhli Tasman; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The background of this research is how the implementation of guidance that done by Department of culture and Tourism Pekanbaru city to the art institutions that registered . Art intitution that are mean here are art galleries. There are four kinds of art gallery in Pekanbaru town which is art gallery of dance, music, theater, and painting. If we observe From what has been done by Department of culture and Tourism Pekanbaru town, the guidance that do can not accepted by all gallery , because the Department of culture and Tourism Pekanbaru only look from saveral gallery. Although all kind of studio responsibility of the Department to be given guidance. But as for factor-factor that affects provide guidance on the formulationart performance this weekend Thursday institutions and has been addressed here is the source of the men that are power has risen and other, communication between the Department of Tourism and Culture in Pekanbaru with sanggar who were coached and the budget a mount of money needed for their activities is financed the training is. From this results can be seen that there are still many studio can not guidance. Even though the studio has been registered in Department of Culture and Tourism. In other words the Department of Culture and Tourism in Pekanbaru not optimal. Keywords : Guidance, institutions art gallery,Sanggar Art